Kingdom of Bahrain : Financial Sector Assessment Program, Detailed Assessment of Observance Assessment of Observance of the CPMI-IOSCO Principles for Financial Market Infrastructures. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This paper provides a detailed assessment of observance of the Committee on Payments and Market Infrastructures-International Organization of Securities Commissions principles for financial market infrastructures (FMIs). Major achievements have been made to establish safe and efficient payments and securities settlement systems in Bahrain. The real-time gross settlement system is highly concentrated and has tight interdependencies with the securities settlement system, making risks management a top priority. The formal assessment suggests that most of the principles are broadly observed, and identifies areas to improve for closer alignment with international standards. The objective of the assessment has been to identify potential risks related to FMIs that may affect financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet